REFORMASI MANAJEMEN PENDIDIKAN (Manajemen Pemasaran dalam Otonomi Pendidikan) - HM, Muh Anwar (Idaarah: Jurnal Manajemen Pendidikan, 2017)
In autonomous era of education these days have developed by educational management base on school. This policy applicated how important school independence in all aspect and process of education. That condition, will touch pattern marking problem of education (promotion), although it was non economic effort units. Educational marking there by represent one of solution in order to developing school arienting to requirement socialization (market).